„Generational disaster” – effects of the Covid-19 pandemic for children - Warzywoda-Kruszyńska, Wielisława; Kruszyński, Kamil (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
The article provides data to illustrate the UN Secretary-General’s thesis of a „generational catastrophe” caused by the COVID-19 pandemic. Children and teenagers suffered this catastrophe, although they are the group least infected with the SARS-CoV-2 virus. The youngest generation is the most numerous group hit by the pandemic. The closure of schools around the world for many months has had short-term effects on students, such as the lack of access to meals offered by educational institutions, which increases the number of malnourished children, as well as far-reaching effects. To overcome them will require time and money, and it will not always be possible. They result from the „educational catastrophe”, i.e. the projected enormous global increase in the number of students below minimal learning proficiency, as the ability to read while understanding simple text. This state of affairs jeopardizes the achievement of the Sustainable Development Goals by 2030, contributing to the deepening of existing inequalities between world regions and within countries. The „generational catastrophe”, the effects of which are postponed in time, is not noticed by politicians, who are preoccupied with ongoing actions to counteract the collapse of the health service and economy. This is reflected, inter alia, in the share of expenditure on education among expenditure on counteracting a pandemic and its economic consequences. The European Union is at the forefront of institutions offering Member States the Next Generation EU financial package for post-pandemic recovery. Unfortunately, the criteria for allocating resources do not require measures to promote the well-being and development of children.